Survival of new firms in the Brazilian franchising segment: An empirical study - Luis Otávio Facanha; Marcelo Resende; Vicente Cardoso; Bruno H. Schröder (Center for Economic Studies and ifo Institute (CESifo), 2011)
The paper investigates survival patterns of Brazilian franchising firms during the 1994-1999 period. First, at a more descriptive level one considered the (percentage) survival of newly created franchisors in the following years. The evidence indicated a drastic decay in survival after only a few years and contrasts with the higher survival of firms in the franchising firms in more developed economies. Survival functions were obtained by means of the Kaplan-Meier estimator for the selected sectors and indicated sharp declines in survival rates over time but with differential patterns across sectors. Finally, an econometric analysis based on Cox's proportional hazard model was considered by exploring explanatory variables pertaining size, age and support regarding legal aspects, location choice and training. The evidence indicates that those supports provided by the franchisor have a positive impact on the probability of survival of new firms whereas there is partial evidence favoring a positive role for firm size on survival.
Keywords: L81; M13; 330; franchising; survival; Franchising; Unternehmensentwicklung; Branche; Betriebsgröße; Schätzung; Brasilien